Slums and metropolis : a sociological study - Bhatt, Manju (New Delhi : Rajat Publications, 2000)
Study of two slums located in Delhi.
Includes bibliographical references (p. [128]-143) and index.
Keywords: Slums -- India; Urban poor -- India; Environmental policy -- India